FACTORS CAUSING SEXUAL HARASSMENT AGAINST TEENAGERS - Ningsih, Widya; Irman, Irman; Yeni, Putri; Myint, Aung; Sharma, Sanjay (Yayasan Minang Darussalam, 2025)
Sexual harassment is behavior or attention of a sexual nature that is unwelcome and undesirable and has the effect of disturbing the recipient of the harassment. Sexual harassment includes, but is not limited to: sexual payment for wanting something, coercion to perform sexual activities, derogatory statements about sexual orientation or sexuality, requests to perform sexual acts that the perpetrator likes, speech or behavior that has a sexual connotation; all can be classified as sexual harassment. This research is normative legal research or library legal research, namely research carried out by examining library materials or secondary data. Secondary data includes: - Primary legal materials, which consist of statutory regulations in this case in the form of: Criminal Code, Law no. 23 of 2004 and other related regulations. - Secondary legal materials, which provide explanations of primary legal materials, such as written works from legal circles, opinions of legal experts. The main motive for the perpetrator to abuse the victim is because the victim responded to the attitude shown by the perpetrator or the feedback shown by the victim. The response intended by the perpetrator is an open attitude shown by the victim, such as frequently replying to the perpetrator's WA chats, smiling and saying hello when they meet, being friendly, appearing seductive according to the perpetrator, and not avoiding being approached by the perpetrator.